Lietuvių literatūrologinės minties dešimtmetis - Norvaiša, Virginijus (Respectus Philologicus, 2001)
This pretty critical article discusses Lithuanian literature science of the last ten years period: it's evaluated as a consequence of Lithuanian thought, which is full of ideologems, myths and rituals, what doesn't allow an important appearance of the modern self-reflection and self-creation. The author of the article, who over-costs the concrete "authorities" (V. Kubilius, V. Daujotytė and others), and announces the danger of the inert and stagnate canons, invites to finish such relations which show unwillingness to accept the very idea of anything that is new; especially he doesn't tolerate the inheritance from sovietic period, which is formatted using different accents.Anyway, separate works of inner cultural changes are very remarkable. Though it's necessary the period of 20 - 30 years for orchard to mature, already today it's possible to talk about the initial features of quality alteration in the literaturology. They are connected with the names of future generations, also with polilogical thinking initiatives by philosophers and culturologists.